Analysis of Genetic Polymorphism and Population Genetic Structure of 57 Autosomal InDel Loci in Beichuan Qiang Population - JIANG Chun-yue; MA Hao; FAN Qing-wei; YANG Hui-ling; XU Dong-dong; WANG Yun; DU Bing (Fayixue Zazhi, 2022)
ObjectiveTo investigate the genetic information of 57 autosomal InDel loci （A-InDels） included in AGCU InDel 60 fluorescence detection kit in the Beichuan Qiang population of Sichuan Province and evaluate its application value in forensic medicine.MethodsA total of 200 unrelated healthy individuals from Beichuan Qiang population of Sichuan Province were typing detected by AGCU InDel 60 fluorescence detection kit. Allele frequencies and population genetic parameters of the 57 A-InDels were statistically analyzed and compared with the available data of 26 populations.ResultsAfter Bonferroni correction, there was no linkage disequilibrium between the 57 A-InDels, and all loci were in Hardy-Weinberg equilibrium. Except for rs66595817 and rs72085595, the minor allele frequencies of 55 A-InDels were above 0.3. PIC ranged from 0.298 3 to 0.375 0, CDP was 1-2.974 8×10-24, CPEduo was 0.999 062 660, and CPEtrio was 0.999 999 999. The calculation of the genetic distance showed that Beichuan Qiang population had the closest genetic distances with Beijing Han and South China Han populations, but far away from African populations.ConclusionThe 57 A-InDels in AGCU InDel 60 fluorescence detection kit have a good genetic polymorphism in Beichuan Qiang population of Sichuan Province, which can be used as effective supplemental for individual identification and paternity identification in forensic medicine.